Latin vulgaire - latin tardif III: actes du IIIème Colloque International sur le Latin vulgaire et Tardif (Innsbruck, 2 - 5 septembre 1991) - Iliescu, Maria (Max de Gruyter, 2010)
Latin Vulgaire - Latin Tardif III: Actes Du III Me Colloque International Sur Le Latin Vulgaire Et Tardif
Includes bibliographical references
Keywords: Konferenzschrift -- 1991 -- Innsbruck; Spätlatein; Vulgärlatein